2021
DOI: 10.1002/nop2.976
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational communication and missed nursing care in oncology wards in Taiwan

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Consistent with the results of Albsoul, the reason for this link may be that the hierarchical system in the medical system destroys the communication between nursing teams or between nurses and doctors, resulting in missed nursing care (Albsoul et al, 2019). Conversely, basic care interventions also affected different dimensions of communication (Pan & Lin, 2021). Managers can create a working atmosphere of equality, In addition, improved communication between nurses and patients increased patient satisfaction but does not reduce omitted care (Prosser et al, 2020), which may be due to the imperfect intervention measures adopted in the study (paper checklists and pencils This study has some limitations.…”
Section: The Impact Of Communication On Missed Nursing Caresupporting
confidence: 71%
See 4 more Smart Citations
“…Consistent with the results of Albsoul, the reason for this link may be that the hierarchical system in the medical system destroys the communication between nursing teams or between nurses and doctors, resulting in missed nursing care (Albsoul et al, 2019). Conversely, basic care interventions also affected different dimensions of communication (Pan & Lin, 2021). Managers can create a working atmosphere of equality, In addition, improved communication between nurses and patients increased patient satisfaction but does not reduce omitted care (Prosser et al, 2020), which may be due to the imperfect intervention measures adopted in the study (paper checklists and pencils This study has some limitations.…”
Section: The Impact Of Communication On Missed Nursing Caresupporting
confidence: 71%
“…Pan & Lin found that both sociodemographic characteristics and work environment factors influenced communication (Pan & Lin, 2021). In terms of sociodemographic characteristics, N3/N4 level nurses and nursing leaders were less satisfied with organizational communication ( p < .05); in terms of work environment, the higher nurses' satisfaction with work environment factors was, the higher their satisfaction with organizational communication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations